A Few Remarks on the Legal Protection of an Individual with Reference to the Discretion of the Administrative Authority - Romaniuk, Paweł (Acta Universitatis Lodziensis. Folia Iuridica, 2023)
This article deals with an extremely important issue concerning the discretion (decision-making freedom) of public administration in the processes of creating legal protection of an individual. These considerations are an attempt to ʽclash’ these two legal categories and they are oriented towards the respect and protection of individual rights. The goal of every law is always man and his good, closely related to the common good. Hence, all symptoms of the administrative authority’s discretion should be directed at attention and care for the interests of the individual, and this, on the one hand, directs, but on the other hand – limits the discretion of public administration activities. A good law is a law favorable to everyone, both for the individual and for society as a whole. In accordance with the adopted assumption, the verification of the objectives of the article justifies the claim that it is necessary to build the right to protect an individual against a decisionmaking tort of public administration that could affect the legal situation of an individual